DNMT3A R882 Mutations Predict a Poor Prognosis in AML: A Meta-Analysis From 4474 Patients. Issue 18 (May 2016) - Yuan, Xiao-Qing; Peng, Li; Zeng, Wen-Jing; Jiang, Bin-Yuan; Li, Guan-Cheng; Chen, Xiao-Ping
Abstract : Abstract: DNA (cytosine-5)-methyltransferase 3 alpha ( DNMT3A ) mutations were widely believed to be independently associated with inferior prognosis in acute myeloid leukemia (AML) patients. As dominant missense alterations in DNMT3A mutations, R882 mutations cause the focal hypomethylation phenotype. However, there remains debate on the influence of R882 mutations on AML prognosis. Thus, this meta-analysis aimed at further illustrating the prognostic power of DNMT3A R882 mutations in AML patients. Eligible studies were identified from 5 databases containing PubMed, Embase, Web of Science, Clinical Trials, and the Cochrane Library (up to October 25, 2015). Effects (hazard ratios [HRs] with 95% confidence interval [CI]) of relapse-free survival (RFS) and overall survival (OS) were pooled to estimate the prognostic power of mutant DNMT3A R882 in overall patients and subgroups of AML patients. Eight competent studies with 4474 AML patients including 694 with DNMT3A R882 mutations were included. AML patients with DNMT3A R882 mutations showed significant shorter RFS (HR = 1.40, 95% CI = 1.24–1.59, P < 0.001) and OS (HR = 1.47, 95% CI = 1.17–1.86, P = 0.001) in the overall population. DNMT3A R882 mutations predicted worse RFS and OS among the subgroups of patients under age 60 (RFS: HR = 1.44, 95% CI = 1.25–1.66, P < 0.001; OS: HR = 1.48, 95% CI = 1.15–1.90, P = 0.002), over age 60 (RFS: HR = 2.03, 95% CI = 1.40–2.93, P < 0.001; OS: HR = 1.85, 95% CI = 1.36–2.53, P < 0.001), cytogenetically normal (CN)-AML (RFS: HR = 1.52, 95% CI = 1.26–1.83, P < 0.001; OS: HR = 1.67, 95% CI = 1.16–2.41, P = 0.006), and non-CN-AML (RFS: HR = 1.96, 95% CI = 1.20–3.21, P = 0.006; OS: HR = 2.51, 95% CI = 1.52–4.15, P = 0.0038). DNMT3A R882 mutations possessed significant unfavorable prognostic influence on RFS and OS in AML patients. Abstract : Supplemental Digital Content is available in the text